Population Genomics of the “Arcanum” Species Group in Wild Tomatoes: Evidence for Separate Origins of Two Self-Compatible Lineages - Florez-Rueda, Ana M.; Scharmann, Mathias; Roth, Morgane; Städler, Thomas (Frontiers in Plant Science, 2021)
Given their diverse mating systems and recent divergence, wild tomatoes (Solanum section Lycopersicon) have become an attractive model system to study ecological divergence, the build-up of reproductive barriers, and the causes and consequences of the breakdown of self-incompatibility. Here we report on a lesser-studied group of species known as the ‘Arcanum’ group, comprising the nominal species Solanum arcanum, S. chmielewskii and S. neorickii. The latter two taxa are self-compatible but are thought to self-fertilize at different rates, given their distinct manifestations of the morphological ‘selfing syndrome’. Based on experimental crossings and transcriptome sequencing of a total of 39 plants representing each species’ geographic range, we provide compelling evidence for deep genealogical divisions within S. arcanum; only the self-incompatible lineage known as ‘var. marañón’ has close genealogical ties to the two self-compatible species. Moreover, there is evidence under multiple inference schemes for different geographic subsets of S. arcanum var. marañón being closest to S. chmielewskii and S. neorickii, respectively. To broadly characterize the population-genomic consequences of these recent mating-system transitions and their associated speciation events, we fit demographic models indicating strong reductions in effective population size, congruent with reduced nucleotide and S-locus diversity in the two independently derived self-compatible species.